Imagining a Makarrata Commission ... - Morris, Shireen; Hobbs, Harry (Monash University, 2023)
The Uluru Statement from the Heart advocates for a First Nations constitutional voice and a legislated Makarrata Commission to supervise agreement-making and truth-telling. A First Nations voice is the immediate priority and the necessary focus of scholarly and practical discussion. However, while advocates envisage a Makarrata Commission being established following a First Nations voice, there is negligible research imagining how a Makarrata Commission might operate. This article addresses that gap. Drawing on agreement-making and truth-telling processes in Australia, Aotearoa New Zealand and Canada, it imagines how a national institution to supervise agreement-making and truth-telling could function. ...